Comparación del fenómeno isla de calor en condiciones de fenómeno del niño en los años 2015 y 2024 en la ciudad de Bogotá, Colombia (2025)
Based on MODIS sensor images, the urban heat island (UHI) phenomenon was identified for the city of Bogotá, Colombia, using surface temperature (LST) data for the years 2015 and 2024 under El Niño conditions. The Google Earth Engine platform was used for image acquisition and processing. A total of 301 images were processed by the platform, resulting in an average temperature of 27.65°C for the year 2015 and 27.18°C for 2024. The main differences were found in the localities of Engativá, Bosa, and Kennedy, compared to Usaquén, Chapinero, Santa Fe, San Cristóbal, and Usme, located adjacent to the city's eastern hills. It is concluded that factors such as population density and the El Niño phenomenon itself contribute to the intensification of urban heat islands (UHI) in the city.